Recent progress in models for electron cyclotron current drive - Marushchenko, N.B.; Beidler, C.D.; Maassberg, H. (Вопросы атомной науки и техники, 2012)
The recent progress in electron cyclotron current drive calculations with the adjoint technique is reviewed. The main attention is focused on such points as parallel momentum conservation in the like-particle collisions and the relativistic effects which are especially important for high-temperature plasmas. For moderate-temperature plasmas, also the finite collisionality effects become to be important. The effectiveness and accuracy of the developed numerical models are demonstrated by ray-tracing calculations.